2020
DOI: 10.1159/000511397
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Elders with Suspected Alzheimer Disease: An Urban Health Centers-Based Study from Iran

Abstract: <b><i>Background/Aims:</i></b> Quality of life (QOL) and Alzheimer disease (AD) among older people have been recognized as public health challenges. Here, we investigated the association between QOL and AD in the elders. <b><i>Methods:</i></b> In this cross-sectional study, elderly people were selected from urban health centers (Shiraz, Iran) by multistage cluster random sampling and were interviewed using LEIPAD (for QOL) and Montreal Cognitive Assessment (for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…This is consistent with the findings of a nationwide cohort study in Korea that included 62,286 participants and found that an increased physical activity level, including a low amount of light-intensity activity, was associated with a lower risk of developing AD [27]. AD was significantly and inversely related to the quality of life, and physical activity and was directly related to age, chronic diseases, and body mass index [7]. In addition, the relationship between quality of life and AD was affected by gender; in men, the quality of life of patients is affected more than women [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the findings of a nationwide cohort study in Korea that included 62,286 participants and found that an increased physical activity level, including a low amount of light-intensity activity, was associated with a lower risk of developing AD [27]. AD was significantly and inversely related to the quality of life, and physical activity and was directly related to age, chronic diseases, and body mass index [7]. In addition, the relationship between quality of life and AD was affected by gender; in men, the quality of life of patients is affected more than women [7].…”
Section: Discussionsupporting
confidence: 90%
“…Since there is no effective treatment for AD, prevention through lifestyle interventions is critical [6]. Health-related quality of life (HRQOL) influences vast aspects of health like physical and mental health, autonomy, social interaction, and the relationship between a subject and their environment [7]. Most patients with AD experience neuropsychiatric symptoms and cognitive impairment during the course of their illnesses, such as apathy, agitation, and psychosis, which negatively affect their HRQOL [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have been conducted to investigate the quality of life of the elderly in this republic such as the study of the association between quality of life and Alzheimer's disease. It is found that 1 in 4 elderly in Iran did not have a preferable quality of life [9]. Cognitive decline, higher risk of falls, daytime tiredness, and decreased physical and mental health are some of the factors that may contribute to the low quality of life in this population [10].…”
Section: Introductionmentioning
confidence: 96%
“…MCI and dementia pose significant challenges to patients, caregivers and healthcare systems due to their rising prevalence and socioeconomic burden, with the numbers of people living with dementia worldwide projected to triple to 152 million cases by 2050 [ 17 ]; furthermore, MCI [ 18 ] and dementia [ 19 ] seriously affect the quality of life and well-being of older adults. In the face of this staggering impact on personal and societal health of these conditions, the therapeutic options are somewhat limited [ 11 , 20 , 21 ], and there is a strong interest in potential strategies for prevention and treatment interventions.…”
Section: Introductionmentioning
confidence: 99%